THE ANALYSIS OF HORIZONTAL DRAIN DESIGN IN SOFT SOIL REINCFORCEMENT - Hafiz Firmansyah; M. Afief Ma'ruf (Universitas Lambung Mangkurat, 2019)
To help the process of consolidation of the soil, On the port access road Trisakti using Prefabricated Vertical Drain (PVD) materials. Of the work (PVD) thing to note is the horizontal drainage, because it was feared the absence of Horizontal Drain work item function of PVD become non-optimal even it might does not work, so the necessary design analysis of Horizontal Drain that can be used on the project. Analysis of Horizontal Drain design is intended to get the Horizontal Drain design alternatives the most optimal based on quality, cost and time.The methods used in the analysis of the design of Horizontal Drain this is a soft soil improvement method using PVD with attention to soil degradation and the planning of the heap.In the design of the installation of PVD method using static, obtained the degree of consolidation of 90% takes 9.33 months. The calculation of Horizontal Drain in the discharge value must be in flush in one horizontal drain line is (minimum permeability). From the results of the analysis there is some material horizontal drain of qualified (in terms of time, cost and quality of workmanship) then get : Rough sand (10.93, Rp. 24.050.000.000,-, and 9.4 months), Fine sand (16.24, Rp-16,835,000,000.0, and 9.4 months), PHD (Horizontal Prefabricated Drain) (74.01, Rp-13,101,140,000.0, and 5.6 months) so that it can be concluded that the material PHD (Horizontal Prefabricated Drain) the most efficient in terms of quality, cost, and time. Keywords: Consolidation, Degrees of consolidation, Horizontal Drain, Preloading, Prefabricated Vertical Drain (PVD), Prefabricated Horizontal Drain (PHD).